2014
DOI: 10.1016/j.rbmo.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal complement and clinical relevance of multinucleated embryos in PGD and PGS cycles

Abstract: The objective of this retrospective study was to investigate the incidence and clinical implications of multinucleation in blastomeres biopsied from cleavage-stage embryos obtained from patients undergoing preimplantation genetic screening (PGS) for aneuploidies or preimplantation genetic diagnosis (PGD) for translocations or single-gene defects (SGD). A total of 3515 embryos were obtained from 306 couples in 380 PGD or PGS cycles. Incidence of multinucleation, chromosomal complement in multinucleated (MN) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Age was not found to affect MNB occurrence in our analysis. The same has been also reported by other investigators [14,17,25]. This may imply that MNB occurrence, similar to ovarian reserve studies (AFC and AMH), is a more appropriate Bbio-marker^of ovarian reserve than age.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Age was not found to affect MNB occurrence in our analysis. The same has been also reported by other investigators [14,17,25]. This may imply that MNB occurrence, similar to ovarian reserve studies (AFC and AMH), is a more appropriate Bbio-marker^of ovarian reserve than age.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, several studies have shown that MNB is largely associated with an increased rate of aneuploidy and chromosomal abnormalities [1,4,16,17,[27][28][29][30][31]. Oocyte chromosomal abnormality is believed to be the main cause of low fertilization, cleavage, and implantation rates in POR cases, demonstrating high incidence of human embryo incompetence leading to low pregnancy and high abortion rates in these women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often such embryos are deselected from fresh transfers, but they may be cryopreserved for a subsequent frozen transfer (4,(13)(14)(15)(16). Trophectoderm biopsies with genetic analysis indicate that not all blastocysts derived from multinucleated embryos have an abnormal chromosome complement (14,17). Our study identified the blastocyst features independently predictive of successful pregnancy and live birth with vitrified-warmed blastocysts.…”
mentioning
confidence: 73%
“…Multinucleation (MN) might decrease the rate of implantation of embryos after their transfer to the uterus, presumably from chromosomal aberrations and/or mosaicism (1)(2)(3)(4)(5)(6)(7)(8). On the other hand, it has been shown that healthy babies can be born from embryos with MN (9,10). Multinucleation might be a result as well as a cause of chromosomal aberrations such as chromosomal instability in Hela cells transfected with Chlamydia trachomatis (11).…”
mentioning
confidence: 99%